2019
DOI: 10.1016/j.jns.2019.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Cost of disease modifying therapies for multiple sclerosis: Is front-loading the answer?

Abstract: There are now over a dozen disease modifying therapies (DMTs) available to treat multiple sclerosis (MS). They vary in efficacy and safety as well as in cost.The literature on the cost effectiveness of these is often confusing and contradictory. There is a lack of quality evidence enabling the comparison of different DMTs. There are scarce randomised controlled trials which look at one DMT compared with another that is not IFN or GA. There is also a lack of systematic reviews comparing the efficacy and safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 127 publications
0
10
0
Order By: Relevance
“…The long-term cost-effectiveness of early versus late use of HE DMTs has been studied in numerous analyses, most of which confirm the positive socio-economic impact of early use of HE DMTs [ 41 ]. It is suggested that initial investment in the early use of HE DMTs may reduce overall costs in the long-term by reducing disability progression [ 41 ].…”
Section: Long-term Pharmaco-economic Assessments May Demonstrate Societal Benefits Of Early and Unrestricted Access To He Dmtsmentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term cost-effectiveness of early versus late use of HE DMTs has been studied in numerous analyses, most of which confirm the positive socio-economic impact of early use of HE DMTs [ 41 ]. It is suggested that initial investment in the early use of HE DMTs may reduce overall costs in the long-term by reducing disability progression [ 41 ].…”
Section: Long-term Pharmaco-economic Assessments May Demonstrate Societal Benefits Of Early and Unrestricted Access To He Dmtsmentioning
confidence: 99%
“…The long-term cost-effectiveness of early versus late use of HE DMTs has been studied in numerous analyses, most of which confirm the positive socio-economic impact of early use of HE DMTs [ 41 ]. It is suggested that initial investment in the early use of HE DMTs may reduce overall costs in the long-term by reducing disability progression [ 41 ]. However, such long-term benefits and savings might be at odds with payers’ short-term budget needs, and, additionally, overall societal costs may be beyond canonical payers’ remit.…”
Section: Long-term Pharmaco-economic Assessments May Demonstrate Societal Benefits Of Early and Unrestricted Access To He Dmtsmentioning
confidence: 99%
“…DMD costs account for most of the direct healthcare costs in MS. They have rapidly risen in the past few years and are expected to further increase among overall expenses, to the point where some studies estimate them to be beyond the health care system tolerance or the generally accepted cost-effectiveness thresholds [ 6 , 7 ]. Some DMDs have been proven highly efficacious, at the expense of potential life-threatening side effects, e.g.…”
Section: Key Summary Pointsmentioning
confidence: 99%
“…Some DMDs have been proven highly efficacious, at the expense of potential life-threatening side effects, e.g. progressive multifocal leukoencephalopathy (PML) for natalizumab, the important lymphopenia for cladribine, ocular disorders for fingolimod, and the increased risk of pulmonary hemorrhages, heart attacks, strokes and cervical-cephalic arterial dissection for alemtuzumab [ 2 , 7 ]. DMD treatment reduces the number of relapses and progression of disability in the short term, and an emerging corpus of data suggests that the onset of a secondary progressive phase can also be delayed [ 8 , 9 ].…”
Section: Key Summary Pointsmentioning
confidence: 99%
See 1 more Smart Citation